Prophetic leadership model: conceptualizing a prophet’s leadership behaviour, leader-follower mutuality and altruism to decision making quality - Nik Maheran Nik Muhammad (2015)
This article advocates that research is lacking on the connection between leadership theory and social network theory. To date, little empirical research has been conducted on leadership and social networks. Thus, the proposition of this article goes beyond traditional leadership models to advocate for a fuller and more integrative focus that is multilevel, multi-component and interdisciplinary, while recognizing that leadership is a complex function of both the organisational leaders and the followers who perform tasks, all of which subsequently leads to decision making qualities. Indeed, the current leadership model focuses on leadership behaviour and the ability to gain followers mutuality, to achieve decision making quality involving the integration of leadership and social network theories. Given the apparent mutable palette of contemporary leadership theory, this emergent construct of the leadership paradigm can expand the poles of the leadership continuum and contribute to a richer and deeper understanding of the relationships and responsibilities of leaders and followers as they relate to decision making qualities. This new construct, which is termed prophetic leadership, explores the literature of the life experiences of the prophet in the ‘Abrahamic Faith’ religion. Drawing on a priori links between the personality trait and spiritual leadership that has recently garnered the interest of scholars, the present study asserts a normative leadership theory that links the personal quality of a leader, posture and principal (based on the Prophet’s leadership behaviour) to synergy and decision making quality. Altruism is proposed to enhance relationships between leadership behaviour and decision making quality. For future research, much work needs to be done specifically aiming to (a) achieve greater clarity of construct definitions, (b) address measurement issues, and (c) avoid construct redundancy.